Lavender marriage perspektif Hukum Keluarga Islam di Indonesia - putri, ahlam dita (Maliki Interdisciplinary Journal, 2026)
The phenomenon of lavender marriage, referring to a marital union between a heterosexual and a homosexual individual for the purpose of concealing one’s sexual orientation, has become increasingly relevant in modern social dynamics. This practice emerges as a response to strong social, cultural, and religious pressures that continue to uphold heteronormativity, particularly in Indonesian society. This article aims to examine the concept of lavender marriage and analyze its compatibility with the principles of Islamic Family Law, especially regarding the validity of marriage contracts and the objectives of marriage within the framework of maqāṣid al-sharī‘ah. Using a library research method, this study reviews academic literature, legal regulations, and previous research related to this phenomenon. The findings indicate that lavender marriage contradicts fundamental Islamic values such as honesty, mutual commitment, and the purpose of establishing a harmonious family (sakinah, mawaddah, wa rahmah). Therefore, this article concludes that lavender marriage is not only socially problematic but also fails to meet the legal and ethical standards required in Islamic Family Law in Indonesia.